Prawo i etyka w medycyniePost-mortem organ donation – legal and ethical questions in Protocol II to EBC on the Transplantation of Organs and Tissues of Human Origin - Skorek, Agata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Additional Protocol II to the Convention for the Protection of Human Rights and Dignity of the Human Being with regard to the Application of Biology and Medicine covers the transplantation of organs and tissues of human origin. One of the most important questions in this subject is the post-mortem aspect of the organ donor’s autonomy, i.e. the form of giving consent to the organ removal. The aim of the article is to show European standards in the field of removal of organs from deceased persons and to underline the fundamental principle of the Convention – the principle of the supremacy of the individual human being’s interest. It is based on the text of the Protocol, particularly articles 16 and 17. Reference is made to opinions of representatives of legal doctrine and the Explanatory Report to the Protocol, which help understand and interpret as well as sets the scope of its provisions, and last but not least to the judgments of the European Court of Human Rights. Functional interpretation plays a particularly important role apart from the linguistic interpretation. Regulations of the Protocol try to balance the individual interest of the deceased donor and – on the other hand – the interest of society continuously demanding organs for transplantation. The Protocol set only the minimum standard of protection; however, the care of the individual’s interest which is of primary importance, is evident. This minimum is a lack of objection.